2016
DOI: 10.1007/s12011-016-0646-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Selenium Supplementation on Seminiferous Tubules and SelW, GPx4, LHCGR, and ACE Expression in Chicken Testis

Abstract: We investigated the effects of dietary selenium (Se) supplementation on the development of chicken testis and the expression of selenoprotein W (SelW), glutathione peroxidase4 (GPx4), luteinizing hormone/choriogonadotropin receptor (LHCGR), and angiotensin converting enzyme (ACE). Sixty roosters were assigned randomly into the control group fed with a basic diet (containing 0.3 mg Se/kg) and the experimental group fed with a diet (containing 0.6 mg Se/kg). The testes were collected individually at age of 6, 9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The GSH-Px is involved in sperm maturation and has a very high activity in the sperm tail structure, which confirms a beneficial role for Se in male fertility ( Khalid et al, 2016 ). These mechanisms may explain the better semen quality in Se-supplemented roosters.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The GSH-Px is involved in sperm maturation and has a very high activity in the sperm tail structure, which confirms a beneficial role for Se in male fertility ( Khalid et al, 2016 ). These mechanisms may explain the better semen quality in Se-supplemented roosters.…”
Section: Discussionmentioning
confidence: 65%
“…In this line, results of this study showed that histological parameters of testis including seminiferous tubule diameter and seminiferous epithelium thickness were improved in SeY0.45 group and other organic Se sources. There is a relationship between increased dietary Se supplementation and enhanced seminiferous tubule diameter and seminiferous epithelium thickness in chicken ( Khalid et al, 2016 ). Supplementation of vitamin E and Se has shown to increase the diameter, thickness, and height of the germinal epithelium of the seminiferous tubules in rat and chicken ( Mehranjani et al, 2009 ; Khalid et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The status of testicle structure and function plays a role in determining the sperm quality, and histopathological alterations in chick testis in the Low-Se group could easily lead to reproductive system dysfunction. Khalid et al (2016) have investigated the effects of dietary Se supplementation on the development of chicken testis, and the results were showed that sufficient Se in the diet could improve the quantity of germ cells and the survivability of supporting cells in seminiferous tubules. These results indicated that Se deficiency could damage testis tissue of chicks, and supplement with an appropriate amount of Se could promote the growth and development of the body and testes to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Khalid et al. (2016) suggested that dietary supplemented Se maintains the normal development of the seminiferous tubules. Khalaf et al.…”
Section: Introductionmentioning
confidence: 99%